Multiple species mating disruption of leafrollers in cherries in Central Otago - McLaren, G.F.; Suckling, D.M.; El-Sayed, A.M.; Hislop, B.T.; Jones, T.F.S. (New Zealand Plant Protection, 2013)
Mating disruption for leafrollers has been conducted on a commercial scale using a single multispecies pheromone dispenser on contiguous blocks of cherries in Central Otago for 4 years Pheromone trap and packhouse results were collected from isolated untreated (654 ha) and pheromonetreated cherry orchard areas (764 ha) in the Cromwell district In untreated cherry orchards catches of light brown apple moth (Epiphyas postvittana) were exceptionally high (38 males/trap/day) with lower catches of Planotortrix octo (025 males/ trap/day) Catches of both species were strongly disrupted in the treated areas reducing E postvittana to 00036 moths/trap/day and P octo to nil Trap catches of both species have increased steadily over 5 years (2008/09 to 20012/13) in blocks not using mating disruption Packhouse results showed that all of the fruit inspected from both treated and untreated areas were free of leafroller infestations in 2012/13 Insecticide use in the pheromonetreated areas was reduced by one application compared with the areas without pheromone